CORPORATE SOCIAL RESPONSIBILITY: EKSPLORASI PERSEPSI, MOTIVASI DAN PRAKTIK - Darsika, A A Made Pradnya; Mahyuni, Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.08.TAHUN 2020DO - 10.24843/EEB.2020.v09.i08.p01, 2020)
This study aims to explore the perceptions, motivations and practices of CSR in the hospitality industry. Case study was conducted at Bali Dynasty Resort. To answer research questions, interviews were conducted with important policy makers who have a good understanding of CSR. The data analysis technique was carried out with four steps namely data collection, data reduction, data display and conclusion drawing / verification. In this study, the data validity test uses reference materials, member checks, triangulation of data sources and triangulation of data collection techniques. This study indicates that the perception of management of Bali Dynasty Resort (1) CSR is about how companies manage business processes to produce an overall positive impact on society; (2) CSR refers to the entrepreneur's obligation to make policies and decisions or follow the desired line of action that leads to goals that are in line with community values; (3) CSR is the way the company manages and repairs social and environmental impacts to generate value for shareholders and stakeholders by innovating strategy, organization and operations; (4) CSR is motivated by internal driven or on the basis of social and environmental responsibility; (5) CSR practices based on the philosophy of Tri Hita Karana.